2016
DOI: 10.1371/journal.pone.0164740
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Evolutionary Origins of Ubiquitous Cu2+ and Zn2+ Binding in the S100 Protein Family

Abstract: The S100 proteins are a large family of signaling proteins that play critical roles in biology and disease. Many S100 proteins bind Zn2+, Cu2+, and/or Mn2+ as part of their biological functions; however, the evolutionary origins of binding remain obscure. One key question is whether divalent transition metal binding is ancestral, or instead arose independently on multiple lineages. To tackle this question, we combined phylogenetics with biophysical characterization of modern S100 proteins. We demonstrate an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 108 publications
4
36
0
4
Order By: Relevance
“…The phylogenetic analyses of the human S100ome resulted in rather ambiguous genealogies, likely due to the young age of the protein family (Fig S17.). Nevertheless, the clade including S100A2, S100A3, S100A4, S100A5, S100A6 was supported with high statistical values in all analyses ( Fig S17.), similarly as it had also been found by others [29,30]. Our functional analysis has revealed that all members of this clade belong to the same subset of the promiscuous group, with a greatly similar functional profile.…”
Section: Function-based Examination Of Relationships Within the S100osupporting
confidence: 88%
See 2 more Smart Citations
“…The phylogenetic analyses of the human S100ome resulted in rather ambiguous genealogies, likely due to the young age of the protein family (Fig S17.). Nevertheless, the clade including S100A2, S100A3, S100A4, S100A5, S100A6 was supported with high statistical values in all analyses ( Fig S17.), similarly as it had also been found by others [29,30]. Our functional analysis has revealed that all members of this clade belong to the same subset of the promiscuous group, with a greatly similar functional profile.…”
Section: Function-based Examination Of Relationships Within the S100osupporting
confidence: 88%
“…It is a Chordata-specific, evolutionary young protein family, and despite the fact that they exhibit moderate sequence similarity, they are structurally very similar owing to their small size (~100 residues) and conserved fold (including two consecutive EF hand motifs) ( Fig S16.). Due to this reason, their phylogenetic analysis generally does not lead to unambiguous results [29,30]. Applying different parameters during the analyses resulted in varied grouping of the human S100ome, moreover only a few clades received statistical supports (see our analyses in Fig S17.).…”
Section: Specificity Map Of the S100omementioning
confidence: 93%
See 1 more Smart Citation
“…Metoden brukes for å påvise spesifikke proteiner i cellen eller på cellemembranen, og er viktig innenfor diagnostikken av cancer, infeksjonssykdom og immunologisk sykdom. CD68 uttrykkes av monocytter og vevsmakrofager (12), CD1a brukes ofte som kjennetegn på dendrittiske celler (13), mens S100 utgjør en gruppe proteiner som er viktige innenfor inflammatoriske sykdommer, kreft og immunforsvaret (14).…”
Section: Figur 3 Skjelettscintigrafi Med Technetium-99 M Som Viser øKunclassified
“…Dyp venetrombose ble bekreftet med ultralydundersøkelse, og det ble samtidig funnet trombocytemi med en trombocyttverdi på 1026 · 10 9 /l (145-390). Hun hadde i tillegg leukocytose med leukocyttverdi på 12,3 · 10 9 /l (3,7-10,0), mens hemoglobinnivået var 13,8 g/100 ml (11,(7)(8)(9)(10)(11)(12)(13)(14)(15)3). Videre utredning påviste JAK2-V617F-mutasjon, og diagnosen essensiell trombocytose ble stilt.…”
unclassified